دراسة دلالية في قصائد من ديوان الخمائل لإيليا أبو ماضي - شيماء قلول (My University, 2026)
Abstract : This study presents asemantic reading of selected poems form the collection(Al-Khamail)by the poet Elia Abu Madi,specifically focusing on three poems :(the winged philosopher),(smile),and(o soul).The significance of this research lies in its attempt to transfer the theory of semantic fields form a conceptual level to an applied level within diaspora poetry(Al-Mahjar),aiming to elucidate its meanings and extract the poet’s creative exprience .The central proplem of study explores the effectiveness of semantic fields in uncovering thecore objectivees of the poems,as well as their role in highlighting the poet’s distinctiveness and clarifying the dimensions of his philosophical vision in the diaspora.To address this problm ,the research plan necessitated dedication of the frist chapter to the theoretical framework of semantics(its definition,subject matter,fields and approaches) ,while the second chapter focused on applying the semantic fieldstheory to the three selected poems. Following this objective analysis,the study yielded several key results ,most notably : the effectiveness of morphological derivatives and semantic phenomema in condensing and guiding meaning,the poe’s mastery in illustrating meaning, and ultimately ,the conclusion that the simplicity of the poet’s language was not accidental,but rather a deliberate stylistic choice reflecting a profound depth of meaning. -------------------- ملخص : تضمنت هذه الدراسة قراءة دلالية لقصائد مختارة من ديوان الخمائل لإيليا أبوماضي، والمتمثلة في ثلاث قصائد هي (الفيلسوف المجنح) ،(ابتسم) ،(يانفس). وتتجلى أهمية البحث في محاولة نقل نظرية الحقول الدلالية من مستوى التنظير إلى مستوى التطبيق على النَّظم المهجري؛ لاستجلاء معانيه واستخلاص تجربة الشاعر الإبداعية فيه .وقد قامت إشكالية الدراسة على البحث في فاعلية الحقول الدلالية في الكشف عن مرامي القصائد ودورها في إبراز خصوصية أسلوب الشاعر واستجلاء أبعاد رؤيته في المهجر. ولمعالجة هذه الإشكالية ،اقتضت خطة البحث أنْ نتناول في الفصل الأول الإطار النظري لعلم الدلالة (تعريفه،موضوعه،مباحثه،مناهجه)، في حين ركزنا في الفصل الثاني على تطبيق نظرية الحقول الدلالية على القصائد الثلاث. وبعد التناول الموضوعي خلصت الدراسة إلى جملة من النتائج، أهمها: فاعلية المشتقات والظواهر الدلالية في تكْثيف المعنى وتوجيه، وبراعة تصوير الشاعر للمعنى ، وصولا إلى أنَّ بساطة لغة الشاعر لم تكن عفوية ، بل هي أسلوب مقصود يعكس عمقا معنويا ------------------------- Rèsumè : Cette étude propose extraits une lecture sèmantique d’un choix de poèmes extraits du recueil (Al-khamail) du poète Elia Abu Madi ,à savoir : (Le philosophe ailé) ,(Souris),et(ô mon âme) .L’importance de cette recherche réside dans la tentative de transposer la théorie des champs sémantiques du niveau théorique au niveau appliqué sur la poésie de la diaspora (Al-Mahjar) ,afin d’en élucider les singnifications et d’en dégager l’expérince créatrice dupoète .La problématique de l’étude s’articule autour de l’efficacité des champs sémantiques à révéler les visées des poèmes ,ainsi que leur rôle dans la mise en valeur de la singularité dupoète et la clarification des dimensions de sa vision philosophique en exil .pour traiter cette porblématique ,le plan de recherche a exigé d’aborder ,dans le premier chapitre,le cadre théorique de lasémantique(sa définition,son objet , ses approches),tandis que le second chapitre s’est focalisé sur l’application de la théorie des champs sémantiques aux trois poèmes . suite à cettte approche objective,l’étude a abouti à un ensembles de résultats, dont les plus importants sont :l’efficacité des dérivés et des phénomènes sémantiques dans la condensation et l’orientation du sens,la dextérité du poète dans l’illustration du sens,pour aboutir enfin au fait que la simplicité du langage poétique n’était pas fortuite, mais relevait plutôt d’un style délibéré reflétant une portée sémantique
Keywords: semantic study; Al-khamail collection; elia abu madi; دراسة دلالية ، ديوان الخمائل، إيليا أبوماضي; étude sémantique; recueil Al-khamail